KARAKTERISASI Al-Zn7 HASIL PELEBURAN DAPUR CRUCIBLE DENGAN TIPE PENUANGAN TUNGKIK - Ipung Kurniawan; Bayu Aji Girawan; Imam Yulianto (P3M Politeknik Negeri Cilacap, 2018)
Nowdays, Alumunium is widely used and utilized in industrial activities because of light properties and having well mechanical strengths. The use of alumunium does not only limit on the use of new alumunium, but also the used one. The main purpose of this research, i.e., (1) testing of physical and mechanical properties of Al-Zn7 from the fussion of Crucible furnace; (2) analyzing crucible furnace of the Al-Zn7 fussion by comparing to the result of the first and second fussion. The method of this research was experimental research with the average value of each the first casting was 49,2 HRB and the second one was 50,3 HRB. Based on the test result showed that the quality of crucible furnace was good because it did not experience the significant changes.